Clinical characteristics of nummular headache and differentiation between spontaneous and posttraumatic variant: an observational study - Javier Trigo; David García-Azorín; Enrique Martinez Pias; Álvaro Sierra; Alba Chavarría; Angel Luis Guerrero (The Journal of Headache and Pain, 2019)
Abstract Background Head trauma has been described as a precipitating event in Nummular Headache (NH). We aimed to describe the largest NH published series and compare characteristics between idiopathic and post-traumatic cases. Methods Patients attended in a Headache Unit in a tertiary hospital (January 2008–January 2018). NH diagnosed according to International Classification of Headache Disorders (ICHD) criteria. We prospectively considered clinical and epidemiological data, comparing idiopathic cases with those precipitated by a cranial trauma. Results We included 225 patients (145 women, 80 men) with NH. Median latency between onset and diagnosis was 10 months (IQR: 5–24). Symptomatic treatment was used in 190 patients (84.4%) among which 142 (74.7%) experienced response to it. Preventive treatment was necessary in 127 patients (51.4%), among which 95 (74.8%) achieved response. 29 patients (23 women, 6 men) described a head trauma related to beginning of pain. When comparing groups with or without previous trauma, age of onset was higher among post-traumatic patients (59.9 ± 17.4 vs 48.1 ± 18 years, p: 0.001). Allodynia upon palpation was encountered more frequently in trauma triggered painful areas (53.3% vs. 32.7%, p: 0.02). No other clinical characteristics differences were observed. Conclusion Cranial trauma is not a rare trigger of NH. Patients with post-traumatic forms are older and the presence of allodynia is more frequent.